2010
DOI: 10.1007/s12011-010-8785-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Selenium Supplementation on Lipid Peroxidation, Antioxidant Enzymes, and Lactate Levels in Rats Immediately After Acute Swimming Exercise

Abstract: The present study aims to evaluate the effect of selenium supplementation on lipid peroxidation and lactate levels in rats subjected to acute swimming exercise. Thirty-two adult male rats of Sprague-Dawley type were divided into four groups. Group 1, control; group 2, selenium-supplemented; group 3, swimming control; group 4, selenium-supplemented swimming group. The animals in groups 2 and 4 were supplemented with (i.p.) 6 mg/kg/day sodium selenite for 4 weeks. The blood samples taken from the animals by deca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…In brain of healthy and mercury-exposed rats sodium selenite did not change MDA concentration (Agarval and Behari 2007). The similar effects were reported by Akil et al (2011a, b) who stated no effect of selenium supplementation (sodium selenite at two different doses: 6 mg/kg/day and 600 μg/kg/day) on MDA values in brain tissue and blood samples, respectively. Sodium selenite did not affect MDA concentration in cerebrum and cerebellum of suckling rats whose mothers were treated with methimazole during pregnancy and lactation.…”
Section: Discussionsupporting
confidence: 88%
“…In brain of healthy and mercury-exposed rats sodium selenite did not change MDA concentration (Agarval and Behari 2007). The similar effects were reported by Akil et al (2011a, b) who stated no effect of selenium supplementation (sodium selenite at two different doses: 6 mg/kg/day and 600 μg/kg/day) on MDA values in brain tissue and blood samples, respectively. Sodium selenite did not affect MDA concentration in cerebrum and cerebellum of suckling rats whose mothers were treated with methimazole during pregnancy and lactation.…”
Section: Discussionsupporting
confidence: 88%
“…There are only a limited number of studies about how selenium, which is known to reduce oxidative damage in exercise, affects glucose metabolism, lactate levels, and tiredness in physical activity [47]. Akil et al [10] investigated the effects of selenium on lipid peroxidation and lactate levels in rats subjected to acute swimming exercise. He reported that the increase in free radical production and lactate levels due to acute swimming exercise in rats might be offset by selenium supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in oxidative stress caused by exercise and the recognition of the stimulation of antioxidant activity by selenium inevitably entails a relation between selenium and exercise [10]. Selenium is also needed for normal testosterone metabolism and testicular morphology, which may explain the presence of several other selenoproteins in the male gonads [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effect of selenium supplementation (0.3 ppm) as selenomethionine (Se-Met) or sodium selenite (Se-Na) in a broiler finishing diet (35 -52 days old) on animal performance parameters: final body weight (g at 52 days old); average daily feed intake (g/d), average daily gain (g/d), conversion efficiency (g gain/g feed) during the period 35 -52 days; and weight of liver and abdominal fat (g) and as a percentage of body weight at 52 days old and carcass yield (%). increased exercise and it was show that selenium supplementation could increase the antioxidant activity in muscle reducing accumulation of lactate and free radicals [32]. Lisuka et al [33] observed a hypoglycemic effect of selenium supplementation and that might be due to the acceleration of glucose metabolism and the inhibition of glucose synthesis in the liver, suggesting a decrease in a source of precursor supply for the gluconeogenesis.…”
Section: Liver Glycogen and Lactate Contentmentioning
confidence: 99%